ONLINE ENGAGEMENT REVISITED USING CONNECTIVISM THEORY - Rahmat, Noor Hanim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Studies on online learning have gone beyond its benefits and drawbacks. This is because many higher institutions are using online learning as part of the learning mode. Many institutions are now using mixed mode (traditional face-to-face and online classes) to impart knowledge to their students. So, when it comes to online classes, the concern is -how are the students engaging in the lessons? This study combines the engagement theory and the theory of connectivism to explore their connections. The study used existing theories to test the model for connectedness in online learning. 100 respondents were conveniently chosen to participate in this study. The instrument used for data collection is the constructs of engagements by Redmond et al. (2018). Data was analyzed using SmartPLS to confirm relationships among variables and to form a model of connectedness. The result of this study reveals the proposed connectivism model for online learning. Findings revealed that there are significant relationships between connectivism and diversity, openness, connectedness, and autonomy. The findings showed there are larger effects of all variables tested. Further tests reveal the goodness of the predicted model. Results of this study bear an interesting theoretical, conceptual, and practical framework for connectedness in online classes. Autonomy, Connectedness, Diversity, Online Engagement, Openness, PLS-SEM